Strategi Pembelajaran Berbasis Montessori Pada Anak Usia Dini - Arsy; Novita Loka; Ayu Era Wardhani; Ayu Lika Rahmadani; Elisa Pitria Ningsih (I'tibar: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Montessori based learning strategies play a crucial role in fostering independence, creativity, and holistic development in early childhood education. The Montessori approach, introduced by Maria Montessori, emphasizes a specially designed learning environment to support children???s natural abilities and developmental stages. This study aims to analyze the implementation of Montessori-based learning strategies in early childhood education in Indonesia, focusing on practical and theoretical aspects. This qualitative research employed a field research approach conducted at Alfath Daycare, an Islamic childcare center. Data collection techniques included direct observation, in-depth interviews with educators and administrators, and documentation analysis. Data were analyzed using Miles and Huberman???s interactive model, consisting of data reduction, data display, and conclusion drawing. The findings revealed that the Montessori strategy significantly contributes to the holistic development of children, particularly in aspects of independence, social skills, and cognitive abilities. Each child???s unique developmental pace is accommodated within this method, which prioritizes tailored learning experiences over standardized approaches. The study highlights the importance of the educator???s role and the learning environment in implementing Montessori principles effectively, alongside identifying challenges such as maintaining consistency in method application and addressing individual needs.